Learning and teaching linear functions [electronic resource] : video cases for mathematics professional development, 6-10 - 220517 Seago, Nanette; Mumme, Judith; Branca, Nicholas (Portsmouth, NH : Heinemann, 2004)
v.1. Facilatator's resource -- v.2. Participant's resource